Endovascular Treatment in the Subclavian Steal Syndrome - Gatto, Luana Antunes Maranha; Chaves, Jennyfer Paulla Galdino; Mendes, Cássio Henrique; Seabra, Diego do Monte Rodrigues; Koppe, Gelson Luis; Demartini Junior, Zeferino (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
When the proximal occlusion or stenosis of the subclavian or of the brachiocephalic artery may require distal arterial filling through reversal flow from the vertebral artery, causing clinically significant blood supply reduction to the brainstem, it is called subclavian steal syndrome (SSS). We report a 54-year-old male patient who presented with multiple episodes of syncopes and vascular claudication due to right SSS. He underwent an angioplasty, evolving with complete improvement of the symptoms. We review the clinical presentation, the diagnostic methods, and the treatment options of the disease.
Keywords: subclavian steal syndrome; subclavian artery stenosis; subclavian steal phenomenon; cerebrovascular circulation; atherosclerosis; syncope